2019
DOI: 10.1080/10826084.2019.1573839
|View full text |Cite
|
Sign up to set email alerts
|

Family structure and past-30 day opioid misuse among justice-involved children

Abstract: Between 2005 and 2010, there were 4,186 calls made to poison control centers for adolescent OM (Sheridan et al., 2016). With this upswing in calls to poison control centers, and even more adolescent opioid-related emergencies going unreported, it is imperative that adolescents are considered when addressing the opioid crisis (Sheridan et al., 2016). In a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…The study found a significant relationship between both age and family structure and OM, which has been noted in recent studies among JIC (Shaw et al, 2019). Shaw et al (2019) found that younger JIC and JIC in grandparent-only households were more likely to meet criteria for P30D OM than single-parent households. Optimism was noted to be extremely significant with wide disparities in rates of OM between JIC that have variable levels of optimism.…”
Section: Synopsis and Interpretationssupporting
confidence: 70%
See 3 more Smart Citations
“…The study found a significant relationship between both age and family structure and OM, which has been noted in recent studies among JIC (Shaw et al, 2019). Shaw et al (2019) found that younger JIC and JIC in grandparent-only households were more likely to meet criteria for P30D OM than single-parent households. Optimism was noted to be extremely significant with wide disparities in rates of OM between JIC that have variable levels of optimism.…”
Section: Synopsis and Interpretationssupporting
confidence: 70%
“…Some of the significant predictors of OM are not mutually exclusive to crimes committed for money or material gain. The current study and previous studies of adolescents have found that Whites, wealthier individuals, and those not living in two-parent households are more likely to misuse drugs (Cicero, Inciardi, & Muñoz, 2005;Karriker-Jaffe, 2011;Shaw et al, 2019). These predictors could also play into the economic compulsive model as JIC with these demographics are more likely to have easy access to quality health insurance through their parents and thereby easier access to prescription opioids.…”
Section: Synopsis and Interpretationssupporting
confidence: 50%
See 2 more Smart Citations
“…Furthermore, the number of mental health diagnoses was recorded via a three-item ordinal measure (0 = none, 1 = one, 2 = two or more) . In the data, FLDJJ researchers combined depression and anxiety [ 28 ]. History of depression/anxiety was measured via an ordinal variable reporting the history of depression and/or anxiety at intake.…”
Section: Methodsmentioning
confidence: 99%